LA SOCIEDAD DEL CONOCIMIENTO, LA BRECHA DIGITAL Y LOS SATÉLITES ARTIFICIALES VENEZOLANOS=THE KNOWLEDGE SOCIETY, THE DIGITAL GAP AND VENEZUELAN ARTIFICIAL SATELLITES - Wright Lascurain, Elizabeth Maite (Cambio Universitario, 2019)
La sociedad del conocimiento, la brecha digital, el futuro de un país está en una generación de relevo capacitada, sin embargo, la realidad supera la ficción. Mucho se ha dicho sobre la sociedad de la información y la sociedad del conocimiento y también no cabe duda que las brechas cognoscitivas y digitales, son una realidad ineludible desde un enfoque prospectivo en materia a la nueva web 2.0, este es el caso de los satélites artificiales venezolanos VENESAT-1 o mejor conocido como: el “Simón Bolívar”, el “Miranda” y el “Sucre”. El primero, se compró para cubrir la brecha digital de Venezuela, lejos de ello se desvirtuó para ser objeto de uso militar y el educativo quedó relegado al simple uso de propaganda. En cuanto al satélite (VRSS-1) o Venezuelan Remote Sensing Satelite (VRSS-1) Satélite “Miranda”, trata sobre imágenes, el uso sobre control de cultivos ilícitos, otras para fines catastrales, y el VRSS-2 “Sucre”. The knowledge society and the digital gap, the future of one country is in a generation of trained relief, however, reality exceeds fiction. Much has been said about the information society and the knowledge society and there is also no doubt that the cognitive and digital gaps are an unavoidable reality from a prospective approach in terms of the new web 2.0 this is the case of Venezuelan artificial satellites, better known as: the "Simón Bolívar", for images the "Miranda" and the "Sucre". The first, the reason for being seemed to cover the digital gap, far from it was distorted to be subject to military use and the educational was relegated to the simple use of propaganda. Regarding the satellite (VRSS-1) or Venezuelan Remote Sensing Satellite (VRSS-1) Satellite "Miranda", it deals with images, its use on control of illicit crops and for cadastral purposes, and eventually the VRSS-2 "Sucre" This last one of images, it is conceived for environmental purposes. We can use these, to meet the "Millennium Goals" in a democratic environment.